Implementasi Manajemen Implementasi Manajemen Kurikulum untuk Meningkatkan Kesiapan Guru terhadap Kurikulum Deep Learning - Heni Widiya Pangesti; Bintun Saniyatus Salamah; Bella Oktania Aslorida; Izza Nafhatin; Silvia Dwi Anjelika (CV.ITTC INDONESIA, 2025)
This study investigates the implementation of Curriculum Management in enhancing teacher readiness for the Deep Learning Curriculum at SD Negeri 4 Bondo, Jepara. The research highlights the critical need to strengthen the principal’s role in supporting teachers to adapt to educational reforms requiring innovation and independent learning. Using a qualitative case study approach, data were gathered through in-depth interviews and literature analysis. The findings indicate that effective Curriculum Management significantly improves teacher readiness. The principal provides strong moral, spiritual, and material support, including monthly teacher learning communities (KOMBEL), access to technology, and budget allocation for professional development. Additionally, the principal actively motivates, mentors, and ensures teachers have access to relevant learning resources. Despite these efforts, challenges remain, such as limited technological infrastructure, insufficient teacher competence in media development, and resistance to curriculum changes. The study concludes that Curriculum Management contributes positively to teacher preparedness for the Deep Learning Curriculum. However, continuous improvement is required in facility support, ongoing teacher training, and strategic leadership to overcome implementation barriers and sustain educational transformation.